Keratin 18 Depletion as a Possible Mechanism for the Induction of Apoptosis and Ferroptosis in the Rat Hippocampus After Hypobaric Hypoxia. (1st March 2023) - Cui, Jinxiu; Ma, Qianqian; Zhang, Chenxu; Li, Yuanzhe; Liu, Juan; Xie, Kangning; Luo, Erping; Zhai, Mingming; Tang, Chi
Graphical abstract: Highlights: Keratin 18 was found as the key gene related to apoptosis and ferroptosis. Apoptosis and ferroptosis coexisted after hypobaric hypoxia exposure. Krt18 may regulate apoptosis and ferroptosis via the JNK signaling pathway. Abstract: Memory impairment is one of the neuropsychological effects of hypobaric hypoxia (HH), which can be associated with programmed cell death, such as apoptosis and ferroptosis. Emerging evidence indicates crosstalk between apoptosis and ferroptosis, while the crosstalk between HH-induced apoptosis and ferroptosis in the hippocampus has not been clarified. Here, microarray profiles were extracted to analyze the differentially expressed genes with and without HH exposure, and keratin 18 ( Krt18 ) was found to be a potential gene related to both apoptosis and ferroptosis. Then, we conducted morphological observations that showed that apoptosis and ferroptosis coexisted in the rat hippocampus after HH exposure. Combined with the real-time q-PCR analysis, the mRNA expression of Krt18 decreased significantly after HH exposure for 1 day and 3 days, and Mapk10 ( JNK3 ) was upregulated at the corresponding time points. After exposure for 7 days, Krt18 and JNK3 showed no significant change. In conclusion, Krt18 may regulate apoptosis and ferroptosis simultaneously, possibly via the JNK signaling pathway, which might provide a potential central target for apoptosis and ferroptosis in hippocampal injury after HH exposure.